PENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN INTEGRAL TAK TENTU MELALUI METODE RESITASI - Heny Karjanto (LPPM UNISDA, 2017)
The research objective of this class action was improving The Student Learning Outcomes Highlights Integral Not Sure Through by The Recitation Method of Class XII TEI SMK Negeri 2 Lamongan in the academic years 2015/2016. This research is consists a class act of 2 cycles. Each cycle consists of four phases. That is planning, acting, observing, reflecting. The object of analysis is students of Class XII TEI SMK Negeri 2 Lamongan in the academic years 2015/2016. Based on the analysis data obtain average 74.64 and completeness of class by 58,33% in the first cycle. In the second cycle the average of students is 78.17 and classroom learning completeness 91,67%. Based on the analysis data, we can conclude that the recitation method can improve student learning outcomes of Class XII TEI SMK Negeri 2 Lamongan in the academic years 2015/2016. Referring to the results of this study, the researcher was recommending to all teachers are using the method of recitation as one as method of learning to improving Student Learning Outcomes.